2018
DOI: 10.1109/tro.2018.2838556
|View full text |Cite
|
Sign up to set email alerts
|

SLAP: Simultaneous Localization and Planning Under Uncertainty via Dynamic Replanning in Belief Space

Abstract: Simultaneous localization and Planning (SLAP) is a crucial ability for an autonomous robot operating under uncertainty. In its most general form, SLAP induces a continuous POMDP (partially-observable Markov decision process), which needs to be repeatedly solved online. This paper addresses this problem and proposes a dynamic replanning scheme in belief space. The underlying POMDP, which is continuous in state, action, and observation space, is approximated offline via sampling-based methods, but operates in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…The pose belief is propagated with Eqs. (5) and (6) if the relative transformation is given in a deterministic form. In our problem, we plan rover's path on a map belief and the uncertainty accumulation only given as a stochastic form.…”
Section: Pose Hyper-belief Propagationmentioning
confidence: 99%
“…The pose belief is propagated with Eqs. (5) and (6) if the relative transformation is given in a deterministic form. In our problem, we plan rover's path on a map belief and the uncertainty accumulation only given as a stochastic form.…”
Section: Pose Hyper-belief Propagationmentioning
confidence: 99%
“…This problem is known in the mobile robotics literature as distributed state estimation. The approach presented herein is similar to recent advancements in linear-Gaussian active sensing that operate in pose-covariance space [2], [3], except that here we propose a novel beliefspace discretization that admits exact value iteration and can be readily incorporated in a hierarchical multi-robot controller, enabling decentralized information acquisition of very large collections of hidden states by large teams of robots.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary version of this work can be found in [1] the covariance matrix. This is the approach followed, e.g., in mobile target tracking [4], [5], sparse landmark localization [1], [6], [7], and active SLAM [3], [8], [9]. Recently, [8] have shown that information-theoretic objectives may fail even to be monotonic in many active sensing tasks, removing performance guarantees for greedy control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations